Correspondances critiques - Frank Müller (Recherches Germaniques)
This article reconstructs a decisive period of the reception of Adorno in France, namely his lectures at the Collège de France in 1961, by following his correspondence with Robert Minder, a French specialist in German studies. Thanks to this dialogue with Minder, Adorno’s critique of the heideggerian language has been strengthened and the foundations of his later work Negative dialectics has been established. In France, a debate on Heidegger followed the lectures of Adorno, as shown at the end of the text.